As particularidades da implementação do REUNI em uma instituição federal - Trevizan, Edevania (Editora Oficina Universitária, 2022)
The Support Program for Restructuring and Expansion Plans for Federal Universities - Reuni was presented as one of the main actions of the Lula government for the expansion of federal public universities. Implementing a set of measures developed since 1990 that aim to maximize education for results through the incessant search for efficiency and productivity in public universities. The program was approved by means of a Federal Decree and points to a structural and curricular reconfiguration of public universities, establishing goals to be met by public universities based on agreements signed between each university and the Ministry of Education. This research proposes to investigate the process and context of elaboration of the higher education restructuring project and the repercussion produced from it in UTFPR. Identifying the changes produced by joining Reuni and evaluating the context and development of Reuni at the university.